HUBUNGAN ANTARA KANDUNGAN SILIKA DENGAN KELIMPAHAN DIATOM BENTHIK DI SEPANJANG SUNGAI PELUS KABUPATEN BANYUMAS - Siti Umiatun; Carmudi Carmudi; Christiani Christiani (Fakultas Biologi | Universitas Jenderal Soedirman, 2017)
Silica is an element that is useful to the organism especially Diatoms (Chrysophyta: Bacillariophyceae). The sources of Silica in waters derive from weathering rock-containing silica. Diatoms are a phytoplankton that able to live as a phytobenthos distributed globally in all types of waters. The purpose of this study was to determine; the silica content, the abundance of diatoms, and the relationship between the content of silica and the abundance of diatoms in the Pelus River Banyumas. This research was conducted as a survey and samples were collected using composite sampling technique at 5 stations. Samples were collected three times with 2 weeks intervals. Two main parameters (diatoms abundance and silica content) and ten supporting parameters (temperature, current velocity, pH, DO, BOD, COD, TSS, TDS, nitrate, and ortofosfat of waters) were measured. Data of analysis calculated in this study including regression correlation analysis to determine the relationship of the silica content and the abundance of diatoms. The silica concentration in the Pelus River waters varies between 112.48-175.00 mg.l-1 with an average of 146 mg.l-1. The total abundance of benthic diatoms was 44,442 ind.cm-2. The highest diatoms abundance was at station II (11,128 ind.cm-2), the lowest was at Station IV (6,828 ind.cm-2). The relationship between silica contained in the waters and abundance of diatoms indicated by the value of R2 (coefficient of determination) by 0.38 or 38%. The abundance of Diatoms are affected 62% by the available silica in the environment, and the rest 38% e rest are determined by other factors.